The Comparison Study of Handgrip Pressure on Steering Wheel National Cars / Mohd Hidayat Ab Rahman ...[et al.] - Ab Rahman, Mohd Hidayat; Maidin,, Nurul Ain; Ahmad,, Mohd Nazri; Osman,, Mohd Hairizal; Wahid,, Mohammad Khalid; Wahid,, Mohd Fa'iz; Firdaus,, Mohamed Saiful; Mohd Yassim, Halyani; Muhammad Damanhuri, Amir Abdullah; Abd Sukor, Siti Marsyidah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The steering wheel is ergonomically designed to provide optimal comfort to the drivers while grip the steering wheel, especially on the long journey. There are significant design differences between the steering wheel car models. Therefore, the objective of this research are to analyze the data of handgrip pressure towards national cars which is Proton and Perodua. The experiment will be performed by using type 2 (two) cars, Proton Saga and Perodua Myvi. Tekscan Grip System is a system that will be used to perform this analysis. Data of handgrip pressure are collected during driving when the device are installed and connect to the respondents. Selection of the road for this experiment will start at 92.1 KM intersection traffic lights, entering North-South Highway, and will end at Tangkak Toll Exit. During the experiment, all volunteers need to maintain speed in the range of 80-100km / h and most of the time, they have to drive in the left lane unless overtaking other vehicles. Distance from beginning to end is about 68.8km and the time taken is about 30 minutes. Drivers will be driving with the hands on the steering wheel 9 and 3 because it is the safest position to hold the steering wheel. The finding from this study will give a better insight on the effect of steering wheel design to the grip pressure of the driver.